Implementation of SDG (Sustainable Development Goals) Program Policies in Gender Equality: a Study in Kumpay Village, Banjarsari District, Lebak Regency - Supriatno, Eko; Lestari, Risma (Ethics and Law Journal: Business and Notary, 2023)
This study examines the implementation of the Sustainable Development Goals (SDGs) program policy in achieving gender equality in Kumpay Village, Banjarsari District, Lebak Regency. The policy implementation refers to Presidential Regulation No. 59 of 2017 concerning the implementation of sustainable development goals aimed at promoting equitable human development and social welfare. The study focuses on how far the SDGs program has contributed to enhancing women’s participation in village development. The research employs a descriptive qualitative method with Edward III’s public policy implementation theory as its analytical framework. Data were collected through in-depth interviews with eight informants representing various community elements and were validated using triangulation techniques. The findings reveal that the implementation of SDGs in promoting gender equality in Kumpay Village remains suboptimal due to low public awareness and limited participation of women in development processes. This condition is influenced by persistent cultural perceptions that confine women’s roles to domestic spheres. The study recommends that both local governments and communities increase their awareness and involvement in promoting gender equality as a vital aspect of achieving sustainable rural development.